Cutaneous pyogranuloma in a cat caused by virulent Rhodococcus equi containing an 87 kb type I plasmid - Farias, M. R.; Takai, S.; Ribeiro, Márcio Garcia [UNESP]; Fabris, V. E.; Franco, S. R. V. S. (Blackwell Publishing, 2007)
A 2-year-old intact male domestic shorthaired cat presented with a chronic, nodular, ulcerated, cutaneous lesion on the right thoracic limb. Histological and cytological examination revealed a pyogranulomatous inflammation with basophilic organisms in the macrophages. A virulent form of Rhodococcus equi containing an 87 kb type I (VapA) virulence plasmid was identified from cultures of biopsy samples. This report describes the clinicopathological features, plasmid profile and virulence of this case of R equi infection.
Keywords: cat; dermatology; bacterial; Rhodococcus; pyogranulomatous